2002
DOI: 10.1016/s0092-8674(02)00835-8
|View full text |Cite
|
Sign up to set email alerts
|

Directed Differentiation of Embryonic Stem Cells into Motor Neurons

Abstract: Inductive signals and transcription factors involved in motor neuron generation have been identified, raising the question of whether these developmental insights can be used to direct stem cells to a motor neuron fate. We show that developmentally relevant signaling factors can induce mouse embryonic stem (ES) cells to differentiate into spinal progenitor cells, and subsequently into motor neurons, through a pathway recapitulating that used in vivo. ES cell-derived motor neurons can populate the embryonic spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

49
1,604
3
12

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,620 publications
(1,685 citation statements)
references
References 61 publications
49
1,604
3
12
Order By: Relevance
“…The application of both RA and Shh during embryoid body formation in murine ESCs was investigated by Wichterle et al [22], Miles et al [23], Kothapalli and Kamm [24], Brown et al [25], and in human ESCs by Li et al [26], Stacpoole et al [27], and Hu and Zhang [28], among others. Such studies have revealed the synergistic effects of these two factors.…”
Section: Introductionmentioning
confidence: 99%
“…The application of both RA and Shh during embryoid body formation in murine ESCs was investigated by Wichterle et al [22], Miles et al [23], Kothapalli and Kamm [24], Brown et al [25], and in human ESCs by Li et al [26], Stacpoole et al [27], and Hu and Zhang [28], among others. Such studies have revealed the synergistic effects of these two factors.…”
Section: Introductionmentioning
confidence: 99%
“…These neurons can be tailored, in cell culture, to display striking morphological and immunophenotypic similarities to cells found in the adult brain, and even to cells lost during the course of brain disease [1][2][3][4][5][6][7][8][9][10] . Because stem cell-derived neurons are born in a culture dish, without the environmental cues of the developing brain, it has become a major quest to determine whether these cells are actually functional, that is, capable of interacting with established neural circuitry.…”
Section: Introductionmentioning
confidence: 99%
“…Given that the goal of early stem cell therapies for ALS were directed at MN replacement, the finding that MNs derived from mouse embryonic stem cells could be grafted into a chick spinal cord and synapse with muscles was exciting [95]; however, results of similar studies in rodent models of ALS were not met with the same success, likely related to features of both ALS, as well as the challenges of reconstructing the motor system as mentioned above. For example, SOD1-G93A rats that underwent grafting of mouse embryonic stem cells into the spinal cord only exhibited a transient motor improvement that may have been due to trophic support provided by the grafted MNs to the degenerating endogenous MNs [11].…”
Section: Transitioning From Early Preclinical Studies To Current Tranmentioning
confidence: 99%